2002
DOI: 10.1161/01.atv.0000037102.31086.f4
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Potentiation of Natriuretic Peptide Limits Polymorphonuclear Neutrophil-Vascular Cell Interactions

Abstract: Objective-Activated polymorphonuclear neutrophils (PMNs) are the main source of circulating neutral endopeptidase (NEP). We tested the hypothesis that NEP inhibition could potentiate the effect of atrial natriuretic peptide (ANP) on PMN-vascular cell interactions in vitro. Methods and Results-ANP alone and its potentiation by retrothiorphan, the NEP inhibitor, significantly inhibited superoxide, lysozyme, and matrix metalloproteinase (MMP)-9 release by N-formyl-Met-Leu-Phe-stimulated PMNs. Activated PMNs degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 46 publications
1
42
0
1
Order By: Relevance
“…It has been recently shown that elastase released by activated PMNs is able to degrade fibronectin 23,39 and provoke SMC anoikis. 23,39 In the present Preincubation of the fibrin matrix with activated PMN releasates (n ϭ 5), luminal extracts (n ϭ 5), or purified elastase impaired BMSCs adhesion, spreading, and growth on the fibrin gel. Cell detachment was prevented by elastase inhibitors ␣ 1 -antitrypsin and SLPI.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been recently shown that elastase released by activated PMNs is able to degrade fibronectin 23,39 and provoke SMC anoikis. 23,39 In the present Preincubation of the fibrin matrix with activated PMN releasates (n ϭ 5), luminal extracts (n ϭ 5), or purified elastase impaired BMSCs adhesion, spreading, and growth on the fibrin gel. Cell detachment was prevented by elastase inhibitors ␣ 1 -antitrypsin and SLPI.…”
Section: Discussionmentioning
confidence: 99%
“…23 Cells were maintained in HBSS. The viability, measured by the release of lactate dehydrogenase (LDH) 29 and purity of the final preparation were greater than 99 and 95%, respectively.…”
Section: In Vitro Studies Of Smc-pmn-fibrin Interactionsmentioning
confidence: 99%
See 3 more Smart Citations